Data supporting 'Two-dimensional perovskite functionalized fiber-type heterostructured scintillators' - Rogers, Edith; Danang Birowosuto, Muhammad; Maddalena, Francesco; Dujardin, Christophe; Pagano, Fiammetta; Kratochwil, Nicolaus; Auffray, Etiennette; Krause, Philip George; Bizarri, Gregory (Cranfield University, 2023)
Data used to produce the article "Two-dimensional perovskite functionalized fibre-type heterostructured scintillators" Data used to create the 2D histograms of charge (fig 2) and the CTR plots (fig 3)
Keywords: 'Emission spectroscopy'; 'Heterostructures'; 'Radioluminescence'; 'Perovskites'; 'Scintillators'; 'luminescence'; 'metamaterials'